Assessment of human parvovirus B19 infection in Egyptian hemodialysis patients. Issue 2 (30th December 2021) - Mohammad, Mai H. S.; Fawzy, Mohamed; Rabie, Abeer G. E.; Attia, Fadia M.; Anani, Maha M.
Abstract: Introduction: Parvovirus B19V has been shown to be associated with end‐stage renal disease (ESRD) with increased risk of post‐infection anemia, especially in hemodialysis (HD) patients. This effect may be due to immunosuppression, insufficient erythropoietin, or short lifespan of red blood cells. Therefore, parvovirus infection should be investigated in this group of patients suffering from anemia or pancytopenia. We assessed the frequency of parvovirus B19 in HD patients attending Suez Canal University Hospital and analyzed the correlation of this infection with hematological parameters in those patients compared with normal individuals. Methods: We recruited 80 ESRD patients on hemodialysis and 70 healthy controls. History‐taking, full examination, and complete blood count (CBC) were performed for all study subjects. Parvovirus B19 detection was performed through polymerase chain reaction (PCR), which included the QIAamp DNA Mini Kit for extracting DNA, which was amplified using TaqMan Universal Master Mix and detected using TaqMan MGB probes by real‐time PCR using Rotor Gene Analyzer (6000). Findings: HD patients had a significantly higher frequency of B19V infection than the control group ( p  = .02). We also found that parvovirus B19‐infected HD patients had significantly lower CBC values than uninfected patients. Conclusion: The frequency of parvovirus B19 was significantly higher in HD patients and was associated with lower hematological parameters than in uninfected patients, suggesting a significant role of this virus in the pathogenesis of anemia and/or pancytopenia in ESRD.